Reducing self-harm in adolescents: the RISA-IPD individual patient data meta-analysis and systematic review - Cottrell, David; Wright-Hughes, Alex; Farrin, Amanda; Walwyn, Rebecca; Mughal, Faraz; Truscott, Alex; Diggins, Emma; Irving, Donna; Fonagy, Peter; Ougrin, Dennis; Stahl, Daniel; Wright, Judy (Health technology assessment (Winchester, England), 2024)
Self-harm is common in adolescents and a major public health concern. Evidence for effective interventions is lacking. An individual patient data meta-analysis has the potential to provide more reliable estimates of the effects of therapeutic interventions for self-harm than conventional meta-analyses, to explore which treatments are best suited to certain groups. A systematic review and individual patient data meta-analysis of randomised controlled trials of therapeutic interventions to reduce repeat self-harm in adolescents who had a history of self-harm and presented to clinical services. Primary outcome was repetition of self-harm. The methods employed for searches, study screening and selection, and risk of bias assessment are described, with an overview of the outputs of the searching, selection and quality assessment processes. Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidance is followed. We identified a total 39 eligible studies, from 10 countries, where we sought Individual Patient Data (IPD), of which the full sample of participants were eligible in 18 studies and a partial sample of participants were eligible in 21 studies. We obtained IPD from 26 studies of 3448 eligible participants. For our primary outcome, repetition of self-harm, only 6 studies were rated as low risk of bias with 10 rated as high risk (although 2 of these were for secondary outcomes only). Obtaining individual patient data for meta-analyses is possible but very time-consuming, despite clear guidance from funding bodies that researchers should share their data appropriately. More attention needs to be paid to seeking appropriate consent from study participants for (pseudo) anonymised data-sharing and institutions need to collaborate on agreeing template data-sharing agreements. Researchers and funders need to consider issues of research design more carefully. Our next step is to analyse all the data we have collected to see if it will tell us more about how we might prevent repetition of self-harm in young people. This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number 17/117/11. A plain language summary of this research article is available on the NIHR Journals Library Website https://doi.org/10.3310/GTNT6331.